Bridging the gaps to overcome major hurdles in the development of next-generation tuberculosis vaccines - Kim, Hongmin; Choi, Han-Gyu; Shin, Sung Jae (Frontiers in Immunology, 2023)
Although tuberculosis (TB) remains one of the leading causes of death from an infectious disease worldwide, the development of vaccines more effective than bacille Calmette-Guérin (BCG), the only licensed TB vaccine, has progressed slowly even in the context of the tremendous global impact of TB. Most vaccine candidates have been developed to strongly induce interferon-γ (IFN-γ)-producing T-helper type 1 (Th1) cell responses; however, accumulating evidence has suggested that other immune factors are required for optimal protection against Mycobacterium tuberculosis (Mtb) infection. In this review, we briefly describe the five hurdles that must be overcome to develop more effective TB vaccines, including those with various purposes and tested in recent promising clinical trials. In addition, we discuss the current knowledge gaps between preclinical experiments and clinical studies regarding peripheral versus tissue-specific immune responses, different underlying conditions of individuals, and newly emerging immune correlates of protection. Moreover, we propose how recently discovered TB risk or susceptibility factors can be better utilized as novel biomarkers for the evaluation of vaccine-induced protection to suggest more practical ways to develop advanced TB vaccines. Vaccines are the most effective tools for reducing mortality and morbidity from infectious diseases, and more advanced technologies and a greater understanding of host-pathogen interactions will provide feasibility and rationale for novel vaccine design and development.